EKSISTENSI PENDETA BUGIS (BISSU) DALAM KEBERTAHANAN TRADISI DI KECAMATAN SEGERI - Ni Wayan Sri Rahayu (Widya Genitri : Jurnal Ilmiah Pendidikan, Agama dan Kebudayaan Hindu, 2021)
This study talks about the survival of the Bugis priest (Bissu) in Segeri District, Pangkejene Kepuluan Regency (Pangkep). In the past, the existence of Bissu was marginalized because it was considered contrary to the teachings of Islam. Now the Bissu begin to show their existence not only in the fields of customs and culture but also in active activities in regional tourism. Researchers try to review the factors that cause Bissu to show its existence, how the role and function of Bissu and the implications of the existence of Bissu in Sagari District. This research uses local historical methods using the theory of existence and role theory. While the research method used is to use historical research methods. The results of the research that can be stated as follows 1) the factors that cause the Bissu in Segeri District can show its existence again, namely the existence of a government policy that is a protection for Bissu to continue to be able to carry out ancient Bugis traditions. It is also influenced by the development of regional tourism. 2) In addition to having a role in traditional ceremonial activities, now the Bissu are also the beauty salon (Indo'Botting), as sanggar guards, and Bissu who participate in the I La Galigo theater activities. 3) The implication of the existence of Bissu in the District of Segeri is that tourism activities can develop well, where the attractions carried out by Bissu are able to attract tourists not only local tourists but also the international level. In addition, with the continued existence of Bissu in Segeri District, traditional Bugis activities and traditions are still maintained today.